ID: 60. Issue 1 (November 2015) - Mossman, Karen; Hare, David; Collins, Susan
<x xml:space="preserve">Abstract</x> Directly sensing virus particles is critical as a first line of antiviral defense, because once allowed to replicate, most viruses will prevent induction of a response. While nucleic acid sensing is sufficient to recognize replicating virus, the genomic material within incoming virus particles is limited and often concealed by viral proteins. We previously found that cells sense membrane perturbation associated with enveloped virus fusion with cellular membranes, leading to induction of a modified, interferon-independent antiviral response. We recently discovered that membrane perturbation by diverse enveloped particles triggers Ca2+ signalling, an essential component of an antiviral response. In addition to Ca2+ signaling, sensing of incoming genomes requires either the cGAS-STING or RLR-MAVS signaling pathway. While viral nucleic acid alone is neither necessary nor sufficient to trigger an antiviral response, Ca2+ oscillations triggered by plasma membrane fusion is also insufficient. Thus, we hypothesize that Ca2+ plays a priming role for the recognition of genomic material within incoming particles, and that cells have evolved novel sensing pathways that recognize the "stress" of homeostasis dysregulation inherent to virus entry. Current studies are aimed at elucidating these novel pathways, particularly mechanisms of activating the key transcription factor IRF3 in the absence of nucleic acid sensing.